FANATISME PENGGEMAR KPOP DALAM BERMEDIA SOSIAL DI INSTAGRAM - Asfira Rachmad Rinata; Sulih Indra Dewi (Master of Communication Science Program, Universitas Diponegoro, 2019)
Abstract. Korean wave has become a big phenomenon in Indonesia, enthusiasm and passion for K-pop culture has led to fanaticism for fans. The distribution of K-pop content on social media such as Instagram gives fans space to participate in supporting their idols and this is one of the factors forming the fanaticism of k-pop fans. This study aims to determine the fanaticism of kpop fans in social media on Instagram as well as how kpop fans respond in responding to hoax and negative information from favorite idols. This research uses descriptive qualitative methods and data collection techniques used are interviews, and literature study. The selection of informants used a purposive sampling technique. The results showed the fact that fanaticism fans in social media on Instagram evaluated through fan activities such as Meaning Making, Meaning Sharing such as interpreting K-pop idol posts as motivation in research, making posts amazed and happy for K-pop idols . Poaching by following fansite accounts and making fanfiction and making videos. Collecting such as uploading pictures about the official kpop merchandise needed and knowledge building with fellow fans. Fanaticism, kpop fans, also through fan responses, asking for information, hoaxes and negatives from their idols responded with many variations such as annoyance, anger until heartache. And to seek clarification of the truth of the news that is by looking at reliable sources such as the official Instagram account K-pop idol, official Instagram account management artist to the Korean major media such as Soompi, Allkpop, and press realease provided by artist management